2019
DOI: 10.15294/rekayasa.v16i2.17515
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kompetensi Guru Dalam Speaking English for Instructional Purposes Untuk Pengajaran Bilingual Di Sd Islam Al Azhar 29 BSB Semarang

Abstract: Memperkuat Sejak tahun 2016, SD Islam Al Azhar 29 BSB Semarang merintis pengajaran bilingual (yaitu, pengajaran dalam dua bahasa, Bahasa Indonesia dan Bahasa Inggris) untuk mata pelajaran Matematika dan IPA. Tantangan utama program ini adalah kompetensi guru dalam berbahasa Inggris. Oleh karena itu, dibutuhkan pelatihan peningkatan kemampuan guru berbahasa Inggris, khususnya Speaking English for Instructional Purposes. Pelatihan yang bertujuan untuk mempersiapkan penyelenggaraan kelas bilingual ini dilaksanaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The researcher concluded that the training would be more successful if the materials were systematically arranged in order based on the teacher's need, evaluated the teachers' result before and after the training, and invited the native speaker to this training. Another research was done by Fitriati and Farida (2017) in one of the private Elementary school in Semarang. The school adopted bilingualdeliver the lesson.…”
mentioning
confidence: 99%
“…The researcher concluded that the training would be more successful if the materials were systematically arranged in order based on the teacher's need, evaluated the teachers' result before and after the training, and invited the native speaker to this training. Another research was done by Fitriati and Farida (2017) in one of the private Elementary school in Semarang. The school adopted bilingualdeliver the lesson.…”
mentioning
confidence: 99%